Aktivitas Antijamur Nanopartikel Zinc Oxide (ZnO) yang Disintesis Menggunakan Ekstrak Kulit pinang Muda (Areca catechu L.) terhadap Candida albicans - Arlimawati Pakpahan; Vera Estefania Kaban; Astriani Natalia Br Ginting (Journal of Pharmaceutical and Sciences, 2026)
Introduction: Infections caused by Candida albicans continue to pose serious clinical problems, largely due to increasing resistance to conventional antifungal drugs and the limited availability of therapeutic options. Therefore, the development of novel, effective, and safe antifungal agents using nature-based nanotechnology approaches is urgently needed. Objective: This study aimed to synthesize Zinc Oxide (ZnO) nanoparticles using a green synthesis method with aqueous extract of young areca nut peel (Areca catechu L.) and to evaluate their antifungal activity against Candida albicans. Methods: The research procedures included raw material and extract characterization, functional group identification using FTIR, ZnO nanoparticle synthesis, and antifungal activity testing using the well diffusion method at concentrations of 25, 50, 100, 125, 250, and 500 mg/mL. Data were analyzed using SPSS at a significance level of 0.05. Results: The biosynthesized ZnO nanoparticles exhibited inhibitory activity against Candida albicans at all tested concentrations. The inhibition zone diameter increased from 12.1 ± 0.65 mm at the lowest concentration to 20.2 ± 1.14 mm at the highest concentration. Statistical analysis revealed significant differences among concentrations (p < 0.05), indicating a clear dose-response relationship.Conclusion: ZnO nanoparticles biosynthesized using young areca nut peel extract possess significant antifungal activity against Candida albicans and have the potential to be developed as an environmentally friendly alternative agent for managing fungal infections. However, further characterization is required to confirm the physicochemical properties of the resulting nanoparticles